The Role of Activity-Based Costing for Assessing and Performance Accounting Costs System to Products Costing Pricing in Manufacturing Environment A case study applying on gadget co - Mousa, Ezzat Kamal Abdalla (Journal of Economic, Administrative and Legal Sciences, 2021)
The study builds for accounting Activity-Based Costing (ABC) analysis supporting decision-making concerning product modularity and the accounting cost system for whether assessing performance to pricing basic and control to the product cost and allocate the activity. the paper aims to investigate the merits. of the Activity-Based Costing (ABC) as a method for assessing the cost consequences of better applied in modularization. This is done through a case study followed by reﬂections on how ABC (might) need to be developed to be able to serve as the relevant costing tool for assessing and performance in cost system and to whether allocate cost to each unit. The second aim some general rules on the cost efﬁciency of modularization from the case study the main problem study ABC is not sufficient enough to applying at any organization that may lower overhead costs. the result of this study The ABC provided the more accurate cost per unit as results good price, sales strategy, performance management and decision making that should be improved It provided much better insight into what drivers overhead costs. ABC recognizes that overhead costs are not all related to production and sale volume applying ABCTD in the manufacturing cost and to whether this more study about ABC in public sectors.